O sabor das imagens - Chiachiri Filho, Antonio Roberto (2008)
In the context of communication and culture, this study is focused on the resources used by photographers specialized in gastronomic photography. The so mentioned resources are responsible for the effects of synesthetic suggestion produced in the message recipient, to the extent of exciting their appetite at times more strongly than a real dish would do. The aim of this work is to show how a flat and bidimentional sign can be able to do this. We are aware that, in this domain, photographic scenario actually concerns a number of simulating resources and powers capable of insinuating delights, triggering and even intensifying psychophysical effects, such as whetting the appetite and stimulating the senses, also causing in an interpreter physical reactions (biophysical, neurosensory, behavioral, etc), such as salivating or imaginably tasting the unique flavor of a certain food according to their previous gustatory background. Based on interviews carried out with professionals working in the production and preparation of gastronomic photography, on analyses of three photographic reproductions from press media specialized in gastronomy and also on bibliographical studies, we believe that this research, carried out under the perspective of Charles Sanders Peirce s semiotics, based on an analysis method taken from Lucia Santaella s work and studies on synesthesia phenomenon, can contribute to the comprehension of a still unexplored aspect of the art of photographic communication, namely, trying to understand how the language of this type of sign, through which gustatory pleasures are evoked by visual message, is structured and works